Enhanced Air Traffic Control Safety Using low Earth orbit Satellites: Non-TCAS Aircraft - Raziq Omayma; Nhaila Hasna; El Khaili Mohamed; Khiat Azeddine (E3S Web of Conferences)
This paper presents a study on a novel TCAS design that combines the exploitation of low-orbit satellites with the existing TCAS system to improve operational efficiency and overcome challenges. With the continuous growth of air traffic, ensuring safety remains a top priority. TCAS was developed to mitigate the risks of aircraft collisions and is mandatory on large transport aircraft. TCAS uses information and data to determine the altitude and relative positions of nearby aircraft. However, despite the advances in air traffic control (ATC) systems, non-TCAS-equipped aircraft continue to operate in the airspace, potentially increasing the risk of mid-air collisions. In addition, existing TCAS systems often generate frequent and unnecessary alarms, especially in densely populated terminal areas, leading to erroneous pilot actions. The proposed solution aims to detect non-TCAS-equipped aircraft by other aircraft, whether they are equipped with TCAS or not. Therefore, the goal is to optimize the efficiency of TCAS to reduce the risk of mid-air collision and improve overall aviation safety. The management applications are distributed on the cloud to save resource exploitation, including energy consumption by processing and air traffic control-related exchanges.